Penentuan Nilai Koefisien Restitusi Kelereng Kaca menggunakan Metode Pencitraan Jeda Waktu Sederhana - Mahendra Kusuma Nugraha,; Ernawatil Gani,; Berton Maruli Siahaan,; Afrioni Roma Rio, (JFT: Jurnal Fisika dan Terapannya, 2024)
Time-lapse imaging has been performed to observe the physical phenomena of imperfect elastic collisions between a glass marble and a tiled floor surface. The glass marble is dropped at a certain height until it hits the floor and experiences repeated rebounds. The event was recorded using the Infinix® Hot S3 smartphone device camera with a shutter speed of 30 frames per second. Analysis of time lapse photography is then carried out using the frame splitting method which is then observed visually to determine the height of each reflection that occurs. The results of the analysis and measurement of the maximum height for the initial state, the first bounce state and the second bounce state are respectively: 15.7 cm, 13.65 cm and 11.45 cm. The coefficient of restitution of glass marbles—based on the data obtained—at the initial maximum height ( towards the first reflection ( ) is ± 0.93242 and the first reflection ( ) towards the second reflection ( ) is equal to. ±0.91587. These results prove that the interaction that occurs is an imperfect elastic collision interaction due to . Keywords: marble, maximum height, restiution coefficient, time-lapse imaging.